A Solvent-Free, Mechanochemical Process for Sustainable Recycling of Neodymium and Dysprosium from E-Waste Magnets - Khairul Raziqin; Arya Ganendra; Abdul Malik (Natural Sciences Engineering and Technology Journal, 2025)
The escalating demand for rare earth elements (REEs), particularly neodymium (Nd) and dysprosium (Dy), for high-performance NdFeB magnets, has created significant supply chain vulnerabilities and environmental concerns associated with primary mining. End-of-life electronic waste (e-waste) represents a substantial secondary resource for these critical materials. This study introduces a novel, environmentally benign approach for recovering Nd and Dy from waste NdFeB magnets. A solvent-free mechanochemical process was developed and optimized. Waste NdFeB magnet powder, sourced from discarded hard disk drives collected in Indonesia, was co-milled with ammonium chloride (NH₄Cl) in a high-energy planetary ball mill. The influence of key process parameters, including milling time (60-360 min), milling speed (200-500 rpm), and the mass ratio of NH₄Cl to magnet powder (1:1 to 5:1), on the extraction efficiency of Nd and Dy was systematically investigated. The structural and morphological transformations were characterized using X-ray Diffraction (XRD) and Scanning Electron Microscopy (SEM) with Energy-Dispersive X-ray Spectroscopy (EDS). Metal recovery was quantified via subsequent water leaching and analysis by Inductively Coupled Plasma-Optical Emission Spectrometry (ICP-OES). The mechanochemical treatment successfully converted the insoluble rare earth phases within the magnet matrix into water-soluble rare earth chlorides. Under optimal conditions—a milling time of 240 minutes, a speed of 400 rpm, and a NH₄Cl-to-magnet mass ratio of 3:1—the process achieved remarkable extraction efficiencies of 98.6% for Nd and 96.2% for Dy. XRD analysis confirmed the transformation of the Nd₂Fe₁₄B phase into REE chlorides, alongside iron and iron boride phases. SEM imaging revealed a significant reduction in particle size and the formation of agglomerated composite particles, crucial for the solid-state reaction. In conclusion, this study demonstrates that solvent-free mechanochemistry is a highly effective and sustainable alternative to conventional hydrometallurgical and pyrometallurgical recycling methods. The process operates at ambient temperature, eliminates the need for corrosive acids and organic solvents, and exhibits high recovery rates, presenting a viable pathway towards a circular economy for critical rare earth elements from e-waste.